2022
DOI: 10.1186/s12889-022-12844-3
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, practice and perceived barriers of natural disaster preparedness among Nepalese immigrants residing in Japan

Abstract: Background Natural disasters have increased during the last several decades all over the world. Due to its geographical and climate conditions, Japan has long been vulnerable to several natural disasters. Coping with disasters is a major challenge overall and even harder for foreigners residing in Japan. Thus, the objective of this study was to examine the perceived knowledge, attitude, practice and perceived barriers of disaster preparedness among Nepalese immigrants in Japan. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…We found that there were higher number of respondents who uses Facebook and other social networking sites or applications to receive information regarding disaster preparedness. The detailed classification of the respondents has been published elsewhere [14].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that there were higher number of respondents who uses Facebook and other social networking sites or applications to receive information regarding disaster preparedness. The detailed classification of the respondents has been published elsewhere [14].…”
Section: Resultsmentioning
confidence: 99%
“…(Table 2) Use of some social networking sites like Twitter and YouTube were associated with the knowledge and attitude level however, it didn't have any associations with their practice level. The detailed multivariable logistic regression model has been published elsewhere [14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample size was calculated based on our repeated measurement with pre-post study design with one pre-intervention measurement and three post-intervention measurements 45 . where, δ plan = mean effect size (40% more than the standard population) 15 , σ plan is the corresponding standard deviation, φ is the 1 as it is pre-post study design and the ratio between pre-test and post-test sample is 1:1, Z 1−α/2 is the 1.96 (α = 0.05), Z 1−β is the 1.28 (β = 0.1), V is the number of measurements before intervention; it is 1 in this study, W is the number of measurements after the intervention; it is 3 in this study, R is the design effect, ρ is the intra-class correlation coefficient; we considered 0.5 as our data are highly correlated.…”
Section: Methodsmentioning
confidence: 99%
“…And there are multiple factors which could determine all kinds of disaster preparedness and not limited to earthquake preparedness like socioeconomic differences, language barriers, races and ethnicity, previous exposure to the disasters, etc. 13 15 . Japan is one of the countries with robust disaster management policies 16 .…”
Section: Introductionmentioning
confidence: 99%